New species of genus Eimeria(Eimeria shivpuri ) in Broiler chicken(Gallus Gallus Domesticus) from Aurangabad (M.S.) India. - Jadhav, B N; Nikam, S V; Bhamare, S N; Jaid, E L (International Multidisciplinary Research Journal, 2012)
The objective of this study was first to investigate the prevalence of poultry coccidiosis and to identify the coccidial species occurring in the study area on local strain .The study involved survey, fecal examination, and identification of coccidial species based on their morphology, predilection site in the intestine and sporulation time.Chicken is more susceptible to Eimeria tenella, Eimeria necatrix, Eimeria brunetti, Eimeria mitis, Eimeria acervulina, Eimeria praecox, Eimeria maxima. During our investigation three new species i.e. Eimeria nikamae, Eimeria tarabaie, Eimeria shivpuri, were recorded in Broiler chicken from Aurangabad district of Maharashtra.